EEG Electrode-induced Skin Injury among Adult Patients Undergoing Ambulatory EEG Monitoring. (2nd October 2019) - Ouchida, Sumika; Nikpour, Armin; Fairbrother, Greg; Senturias, Maricar
ABSTRACT: Introduction : Ambulatory electroencephalography technology has improved in the last 40 years. Many clinicians believe that some skin injury is an unavoidable complication of prolonged EEG monitoring. In this study, we examined potential risk factors associated with electrode-induced skin injury in adult patients with AEEG monitoring. Methods : A cross-sectional observational study was conducted from December 2017 to October 2018, in the outpatient clinic at a teaching hospital in Sydney, Australia. Patients were included if they were older than 16 years of age and had been referred for AEEG monitoring of two to five days duration. Trained neurophysiology nurses completed a pre-application skin assessment before they applied the EEG electrodes. Daily assessments of the skin condition were conducted. The patients completed a questionnaire to assess comfort levels at the completion of the testing. Results : A total of 251 patients participated in this study. Two groups were established – those who were monitored for 2–3 days (Group 1; n = 92) and those who were monitored for 4–5 days (Group 2; n = 159). There was a significant acceleration in inflammation which occurred between day 2 and day 4/5. Cross-sectional analyses of patient characteristics showed that increasing age, fair skin color, dry skin texture and fine hair texture were the prevailing risk factors for greater inflammation scores. Conclusion : The patient discomfort and inflammatory burden associated with this procedure were high. Inflammation was shown to increase with the duration of electrode application.